2012
DOI: 10.1039/c2cc16654b
|View full text |Cite
|
Sign up to set email alerts
|

Light-activatable molecular beacons with a caged loop sequence

Abstract: We have synthesized molecular beacons with caged nucleobases in the loop region. These constructs remain non-fluorescent in the presence of their target RNA but can be fully activated by light (366 or 405 nm) in vitro and in HEK293 cells. We suggest that this technology will be useful for single molecule RNA tracking in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
1
42
0
3
Order By: Relevance
“…Two approaches exist for this up to now (Figure 7): Tan and co‐workers showed that such an effect can be realized by connecting the two ends of a molecular beacon through a photocleavable linker 180. In our study we demonstrated that the effect can be improved to an almost binary ON/OFF behavior if the nucleobases in the loop region are caged with multiple cages which could still be removed efficiently 181. Abe, Ito, and co‐workers showed that a similar effect is possible when using an oligonucleotide with a caged fluorophore 182.…”
Section: Irreversible Photo(de)activation (Uncaging)mentioning
confidence: 64%
“…Two approaches exist for this up to now (Figure 7): Tan and co‐workers showed that such an effect can be realized by connecting the two ends of a molecular beacon through a photocleavable linker 180. In our study we demonstrated that the effect can be improved to an almost binary ON/OFF behavior if the nucleobases in the loop region are caged with multiple cages which could still be removed efficiently 181. Abe, Ito, and co‐workers showed that a similar effect is possible when using an oligonucleotide with a caged fluorophore 182.…”
Section: Irreversible Photo(de)activation (Uncaging)mentioning
confidence: 64%
“…A pulse of light, however, cleaved a photosensitive linker, thus forcing the MB probe to report the presence of the analyte. Another example of a light-activatable MB probe was reported by Joshi et al [138]. In their design, the loop sequence was equipped with caged nucleotides that could not form Watson-Crick base pairs.…”
Section: Recent Variations Of Mb Probesmentioning
confidence: 99%
“…Irradiation of caged compounds, which releases the protected specic functional groups, has been employed to locally control biochemical properties of hydrogels. [49][50][51][52] Hydrogels will be degraded when irradiated with cytocompatible doses of long wavelength UV, visible, or two-photon IR light (365, 405, and 740 nm, respectively), enabling precise control over hydrogel degradation proles in situ. 53 This photodegradation scheme was successfully applied to control the spreading of human mesenchymal stem cell (hMSC) within light-eroded channels.…”
Section: Introductionmentioning
confidence: 99%